2023
DOI: 10.1021/acs.energyfuels.2c03680
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Carbon Storage Process from Flue Gas Streams Using Rice Husk Silica Nanoparticles: An Approach in Shallow Coal Bed Methane Reservoirs

Abstract: Carbon capture and storage (CCS) is considered a key process to reach net-zero emission by the 2050 aim of limiting global warming. Coal bed methane (CBM) is considered potential geological reservoirs for underground CCS due to the CO2–CH4 exchange feasibility by adsorptive phenomena. Global implementation has been focused only on deep reservoirs to provide methane recovery. Thus, this work proposes a modified CCS process based on silica nanoparticle inclusion for shallow CBM reservoirs (<300 m). The nanomater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…The storage behavior of shallow and low-pressure sequestration of CO 2 in coal seams is of particular interest as a result of its shallow injection depth compared to that of other reservoirs. For instance, Giraldo et al 155 proposed an improved carbon capture and storage (CCS) process based on the inclusion of silica nanoparticles as additives for shallow coalbed methane reservoirs with a depth less than 300 m. The silica nanoparticles were employed to enhance the adsorption capacity of the coal seam. The results showed that the treated samples exhibited an increase in adsorption capacity of over 1000%.…”
Section: Recent Research Hotspotsmentioning
confidence: 99%
“…The storage behavior of shallow and low-pressure sequestration of CO 2 in coal seams is of particular interest as a result of its shallow injection depth compared to that of other reservoirs. For instance, Giraldo et al 155 proposed an improved carbon capture and storage (CCS) process based on the inclusion of silica nanoparticles as additives for shallow coalbed methane reservoirs with a depth less than 300 m. The silica nanoparticles were employed to enhance the adsorption capacity of the coal seam. The results showed that the treated samples exhibited an increase in adsorption capacity of over 1000%.…”
Section: Recent Research Hotspotsmentioning
confidence: 99%
“…Reference conducted an experiment to investigate the effects of nanoparticle application in CO 2 sequestration in shallow CBM reservoirs (<300m). Different rice husk silicas (RSi) were used to observe their effects on enhancing sorption capacity, which was synthesized from a local Colombian mill.…”
Section: Nanotechnology Application During Co2 Sequestration In Shall...mentioning
confidence: 99%
“…Chemical structures of used modifiers: (a) urea, (b) ethylenediamine, (c) diethylamine, and (d) triethylamine. This figure was reproduced with permission from ref . Copyright 2023 American Chemical Society.…”
Section: Nanotechnology Application During Co2 Sequestration In Shall...mentioning
confidence: 99%
“…35 The interaction between CO 2 , CH 4 , and water molecules 36 leads to significant changes in the ultimate macromolecular structure, natural fracture structure, pore structure, and mineral phase of coal, 37−41 and the temperature and pressure of coal storage can affect the effectiveness of CO 2 storage. 42,43 Many scholars have improved the CCS process through nanotechnology, such as Giraldo's 44 proposal of an improved CCS process based on silica nanoparticle inclusions, which enhances the adsorption of CO 2 in the mixture (CO 2 −N 2 ).…”
Section: Introductionmentioning
confidence: 99%